Pencemaran Lingkungan Hidup Di Provinsi Jawa Timur Menurut Ketentuan Undang-Undang Nomor 32 Tahun 2009 Tentang Perlindungan Dan Pengelolaan Lingkungan Hidup Ditinjau Dari Penegakan Hukum Administrasi Lingkungan - Galuh Lintang Taslim (Darma Cendika Catholic University, 2015)
During the development of technology and industry, Indonesia is one country that is very fast. Increasing number of industries that have sprung up that aims to meet the needs of an increasingly diverse society and rising. Technological development and advancement of the industry will have an impact on the quality of the environmental carrying capacity, which in turn will damage the environment itself. Exploitation of natural excessive with little regard for sustainability carried out by a group of people for the sake of right must be stopped, because it will cause damage to the environment, because it can not deny later if the industry will have a negative impact on the environment originating from industrial activities generating waste, and a large amount of various kinds which will pollute the environment.